2021
DOI: 10.3389/fonc.2020.627379
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Spread in Prostate Cancer Patients Influencing Radiotherapy Response

Abstract: Radiotherapy and surgery are curative treatment options for localized prostate cancer (PCa) with a 5-year survival rate of nearly 100%. Once PCa cells spread into distant organs, such as bone, the overall survival rate of patients drops dramatically. The metastatic cascade and organotropism of PCa cells are regulated by different cellular subtypes, organ microenvironment, and their interactions. This cross-talk leads to pre-metastatic niche formation that releases chemo-attractive factors enforcing the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 275 publications
(273 reference statements)
0
31
0
Order By: Relevance
“…Bone metastasis is the most common type of PC metastasis. The invasion of prostate cancer cells on other organs such as liver, lung, kidney and adrenal glands has also been reported (39). Moreover, although the prognosis of PC has improved in recent years, a large number of PC patients are not responsive enough to androgen deprivation therapy (ADT) and these patients are often considered as endocrine-independent PC.…”
Section: Discussionmentioning
confidence: 99%
“…Bone metastasis is the most common type of PC metastasis. The invasion of prostate cancer cells on other organs such as liver, lung, kidney and adrenal glands has also been reported (39). Moreover, although the prognosis of PC has improved in recent years, a large number of PC patients are not responsive enough to androgen deprivation therapy (ADT) and these patients are often considered as endocrine-independent PC.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical study with [ 131 I]I-PSMA ligand also addressed the bone marrow toxicity as being problematic [ 5 ]. Nevertheless, a Phase II study with [ 131 I]I-MIP-1095 is ongoing and might reveal the clinical potential of using 131 I-based radiopharmaceuticals for aggressive metastatic prostate cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The required dose increase is more than twofold and it further increases depending on the number of tumors observed, as well as the metastatic dissemination pattern. The first randomized Phase III clinical trial, VISION, has concluded patient inclusion and first results are expected in the near future [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, α-emitters have been postulated as ideal radionuclides for the treatment of cancer [154][155][156][157]. In particular, the treatment regimen for disseminated and poorly differentiated metastatic disease, e.g., PSMA(+) mCRPC, might highly benefit from targeted α radionuclide therapy (TAT) [158]. Recently, extensive efforts have been made to review in detail α-emitter-based radiotherapeutic approaches for PC [159].…”
Section: Alpha (α)-Based Targeted Radionuclide Therapymentioning
confidence: 99%